“Investigação de parâmetros dielétricos para otimização de processos biotecnológicos” - Taques Filho, Eduardo Gaspar Ribeiro (2021)
The knowledge of interactions and reflections of chemical changes in the environment through dielectric parameters allows a greater understanding of microwave chemistry and provides conditions for the proposition of new methods, new reactions and the design of reactors aimed at expanding the scale of analyzed reactions. It can be observed that in the reactions involving transesterification, dielectric measurements were evaluated against the behavior of chemical transformations for methyl and ethyl reactions, using 4 acid catalysts (H2SO4, H3PO4, ClSO3H and CH3SO3H) and with different raw materials (Brazil Nut, Soy and Babassu Oils) within the frequency range of 0.3 to 13 GHz. The frequency dependence was observed in the dielectric properties of the reaction and these still varied considerably in function of the increased conversion to biodiesel. Therefore, it was found that the presence of free fatty acids and water in the reaction medium also contribute considerably to the dielectric behavior for such reactions. For the solketal production reactions, the dielectric parameters of the pure constituents (glycerin, acetone, solketal), of mixtures involving solketal/water/acetone/H2SO4 and of the reaction medium during the reaction submitted to conventional heating were obtained. Thus, when monitoring the reactions, a high loss tangent (0.2 <Tg δ <0.4 to 2.45 GHz) was observed, which reflects in the high energy absorption and allows overcoming the long conventional heating times. The dielectric parameters of the plants were obtained to evaluate their interaction with microwaves and thus study the dependence of the proportion of water used in the process of extracting essential oils. For citronella, eucalyptus and piperaceae (stem and leaves) the dry material was measured in mixtures with water in a 1:1 ratio, for guarana (bark and grain) it was measured in plant-solvent mixtures (16g:320g) being the solvent ethanolwater (1:1) and for the fruit of the Brazil nut, measurements of the husk of the seed and almonds were carried out. The measurements of botanical materials showed constant lows and dielectric loss due to the great complexity of their constitution, which were dependent on the frequency and temperature used. With the increase in temperature for the dry samples, there was a direct increase in the aforementioned parameters, due to the increase in the degree of agitation of the molecules, which allows for greater rotation/mobility of the same. The measurements with the addition of water showed considerable alteration, change in the behavior of the curves, due to the great difference in the values between water and the plant alone, and a significant increase in the values of constants and dielectric losses depending on the amount of added water.